Edukasi Keselamatan dan Kesehatan pada Tempat Kerja bagi Alumni Kesehatan Masyarakat Universitas Negeri Malang - Septa Katmawanti, S.Gz., M.Kes; Lucky Radita Alma, S.KM., M.PH; Windi Chusnia Rahmawati, S.KM., M.Kes; Selsa Tri Septiani; Azza Rizqia Vatrisa; Anita Sulistyorini (Warta LPM, 2024)
The incidence of occupational diseases and work accidents has increased every year. This can occur due to the lack of optimal implementation and implementation of the Occupational Safety and Health Management System (SMK3) in the workplace or even the implementation of SMK3 in the workplace. The application of SMK3 in the workplace is very vital, its urgency and usefulness. Based on the results of a situation analysis survey to UM Public Health Alumni, many workplaces have not been optimal in implementing SMK3 and even some workplaces have not implemented SMK3. As a promotive and preventive means, the FIK UM community service team created a digital training activity for UM Public Health alumni which was carried out in the form of an after sales webinar which aimed to increase knowledge and strengthen the knowledge of UM Public Health alumni. The activity consists of 6 series with the main theme being the Occupational Safety and Health Management System, taking place from June to July 2023 with different topics and speakers in each series. Evaluation of activities is carried out based on pretest and posttest results as well as participant satisfaction surveys. Based on the results of the analysis, it is known that the implementation of this after sales webinar succeeded in increasing participants' knowledge related to the Occupational Safety and Health Management System to reach 73.5%. Also, 73% of participants who participated in digital training activities were very satisfied with the implementation of this activity.